Faktor-Faktor Yang Mempengaruhi Harga Saham Di Perusahaan Manufaktur Periode 2015-2017 - Divani Thalia Budiarto, Herlin Tundjung Setianingsih (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is to describe how much influence of accounting earnings, leverage, and firm size have on stock prices in manufacturing companies in the consumer goods and various industrial sectors listed on the IDX 2015-2017. The consumer goods industry and various industries add up to 81 of the listed.. The selection of samples that used was purposive sampling andhe analysis was carried out using Statistical Products and Services Solutions (SPSS).. The results from regression analysis is accounting earnings have a positive and significant effect on stock prices, leverage has a positive and not significant effect on stock prices, and firm size has a positive and significant effect on stock prices